GOOGLE SITES-BASED LEARNING MEDIA IN NATURAL SCIENCE LESSONS IN ELEMENTARY SCHOOL : A LITERATURE STUDY - Rahindra, Rahadian; Maksum, Arifin; Aruwiyantoko, Anggit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
The writing of this article aims to review various journal articles on the development of learning media based on Google Sites in learning Natural Sciences in elementary schools. The method used in writing the article is a literature study of articles that have been published in the period between 2020 and 2025. The results of the study state that there is feasibility in learning science at the elementary school level using Google Sites-based learning media. Validity assessments from media experts and material experts are on average in the